Mencukur Rambut Bayi Perempuan Saat Akikah Perspektif Mazhab Imam Ahmad bin Hanbal - Rosmita Rosmita; Sirajuddin Sirajuddin; Nurul Qisti; Nasaruddin Nasaruddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2022)
This study aims to find out the problems of shaving hair for babies at the time of aqeekah among the scholars, as well as to find out the views of the Imam Aḥmad bin Hanbal school and its legal isntinbat method in the issue of shaving hair for baby girls in aqeekah. This research is a type of descriptive literature research, which focuses on the study of text manuscripts, using a normative juridical approach. As for the results of the research that scholars have different opinions regarding the law of aqeekah, some say that it is sunnah muakkadah and some say that it is obligatory, in the implementation of aqeekah it is sunnah to perform all rituals of aqeekah. As for the wisdom, it is prescribed for aqikah that there are many benefits, as a form of gratitude to Allah swt, the conditions for akikah are the same as those for qurban and there is no difference of opinion on this matter. In the istinbat method, Imām Aḥmad bin anbāl from the prophet's hadith as well as the opinion of scholars, it is seen that shaving the hair on babies is only for male babies, so that female babies are not included in the order, so they are judged differently from the law for male babies. Regarding this, the opinion of Imam Ahmad bin Hanbal views that it is makruh to shave a baby girl's hair